The economic implications of integrating green accounting practices in Middle Eastern financial institutions: Challenges and opportunities - Ewis, Hanan Fouad Mahmoud; Ghanem, Samar Atef (Edelweiss Applied Science and Technology, 2025)
This paper presents a discussion on the economic consequences of integrating green accounting practices in financial institutions within the Middle Eastern region. Green accounting is increasingly regarded as a tool for sustainability and environmental risk management, but so far its implementation in the region remains very inconsistent. Key challenges identified that hinder the full implementation of green accounting practices include financial constraints, a lack of skilled professionals, and regulatory uncertainties. At the same time, it presents certain excellent opportunities that will include an enhanced corporate reputation, easy access to green financing, and better compliance with future environmental regulations, thereby creating long-term economic benefits. The study also identifies increased awareness, training programs, clearer regulatory frameworks, and technological solutions as necessary for facilitating the widespread adoption of green accounting. Addressing these challenges and capitalizing on the related opportunities will provide financial institutions in the Middle East with the chance to improve their financial performance, gain access to eco-conscious investors, and achieve long-term organizational sustainability. The findings provide useful insights for policymakers, financial institutions, and sustainability experts on how green accounting can help attain economic growth and sustainability in the region.